Aspects Allocentristes de l'Humanisme dans l'Univers Romanesque de Williams Sassine - Dami, Emmanuel Naancin (Rhodes University, Faculty of Humanities, School of Languages, 2018)
The human being, his behaviour and more importantly, his very essence have, for time immemorial, proven to be enigmatic to many a man and to researchers in particular. Consequently, the need for a thorough and more profound understanding of man has made him the epicentre of epistemic investigations across many academic disciplines. This, unfortunately, does not seem to have shaded bright lights on the grey areas bordering on his nature to his behavior. This, in turn, opens up other windows requiring further probes. For instance, proponents of the Neo-classical economic school contend that the human being is homo oeconomicus. This implies that man is intrinsically egocentric and a rational being whose decisions are based on informed choices driven by his urge for maximal utility geared towards his personal satisfaction (O'Boyle 2009; Caruso 2012). This stance invalidates man's ability to do 'disinterested good' in any form. African francophone literature is replete with different and diverse images of man, his behaviour and existential conditions: sufferings and struggles. It, therefore, constitutes, inter alia, a laboratory in which researchers undertake investigative endeavours. This thesis beams its floodlights on the allocentric aspects of humanism in the novels of Williams Sassine. Thus, using the phenomenological and 'clavieniste' lenses as overarching operational theories, the thesis investigates Sassine's novels with the view to shading a ray of light on the 'humanistic man' especially the allocentric dimensions of his nature and comportment. Emphasis is laid on the motives and motivations underlying the individual and the in-group struggle of the sassinien heroes in the emancipation of their society from the shackles of colonial and postcolonial domination, exploitation and subjugation resulting in self-determination and the subsequent disenchantment. Furthermore, the thesis examines the nature and character of human charity, generosity and sacrifices among the characters in the novels. In conclusion, the thesis establishes, through an x-ray of the nature of actions and decisions of certain characters in the novels, the examination of the conscious and subconscious intentions underlying these same actions and decisions which, on a face value, are apparently altruistic, that the sassinien heroes' efforts and sacrifices are geared towards the common and greater good. This invariably means that man is, indeed, capable of posing disinterested acts of charity and bringing succour, devoid of any ulterior motives for personal gain, to his fellow humans. The position of the Neo-classical economists is consequently over-assuming, sweeping and tad generalizing. The sassinien characters have demonstrated beyond reasonable doubt that they are humanists. Their nature, the remote and immediate causes of their fights, the goals and objectives of their struggles and their spirit of abnegation have indeed proven that "human beings have the right and the responsibility to give meaning and shape to their own lives. [They have stood] for the building of a more humane society through an ethics based on the human and other natural values in a spirit of reason and free inquiry through human capabilities" (AHA 2017 : 3).
Allocentric aspects of humanism in the novels of Williams Sassine
Keywords: Sassine, Williams, 1944-1997 -- Criticism and interpretation; Guinean fiction (French) -- 20th century -- History and criticism; Humanism in literature; Human beings in literature; Postcolonialism in literature; Existentialism in literature